Effects of pharmacologically induced Leydig cell testosterone production on intratesticular testosterone and spermatogenesis. Issue 2 (2nd September 2019) - Chung, Jin-Yong; Brown, Sean; Chen, Haolin; Liu, June; Papadopoulos, Vassilios; Zirkin, Barry
Abstract: The Leydig cells of the mammalian testis produce testosterone (T) in response to luteinizing hormone (LH). In rats and men with reduced serum T levels, T replacement therapy (TRT) will raise T levels, but typically with suppressive effects on sperm formation. The rate-determining step in T formation is the translocation of cholesterol to the inner mitochondrial membrane, mediated by protein–protein interactions of cytosolic and outer mitochondrial membrane proteins. Among the involved proteins is cholesterol-binding translocator protein (TSPO) (18 kDa TSPO). We hypothesized that in contrast to TRT, the administration of the TSPO agonist N, N -dihexyl-2-(4-fluorophenyl)indole-3-acetamide (FGIN-1-27), by stimulating the ability of the Leydig cells to produce T, would result in the elevation of serum T levels while maintaining intratesticular T concentration and therefore without suppression of spermatogenesis. Age-related reductions in both serum and intratesticular T levels were seen in old Brown Norway rats. Both exogenous T and FGIN-1-27 increased serum T levels. With exogenous T, serum LH and Leydig cell T formation were suppressed, and intratesticular T was reduced to below the concentration required to maintain spermatogenesis quantitatively. In contrast, FGIN-1-27 stimulated Leydig cell T formation, resulting in increased serum T without reductions in intratesticular T concentrations or in testicular sperm numbers. FGIN-1-27 also significantly increased serum and intratesticular T levels in rats made LH-deficient by treatment with the gonadotropin-releasing hormone antagonist cetrorelix. These results point to a possible approach to increasing serum T without negative effects on spermatogenesis, based upon stimulating T production by the Leydig cells themselves rather than administering T exogenously. Abstract : Summary sentence : The TSPO agonist FGIN-1-27 stimulates the ability of the Leydig cells producing testosterone and results in elevating serum and intratesticular testosterone without negative effect on spermatogenesis.